William of Orange in France and the Transnationality of the Sixteenth-Century Wars of Religion - van Tol, Jonas (BMGN - Low Countries Historical Review, 2019)
William of Orange’s French campaign of 1569 is one of the most curious and least-understood episodes in the life of the leader of the Dutch Revolt. The confusion over his motives for participating in the wars in France arises from the longstanding tendency to see the Dutch Revolt and French Wars of Religion as similar but separate conflicts. Yet Orange regarded them fundamentally as manifestations of the same struggle. This article unpacks the development of Orange’s transnational outlook during the decade leading up to his French campaign – an outlook that was shared by many of his peers in the Low Countries and beyond and that shaped the course of the French Wars of Religion and the Dutch Revolt. Willem van Oranjes veldtocht in Frankrijk in 1569 is een van de meest curieuze en slechtst begrepen episodes uit het leven van de leider van de Nederlandse Opstand. De verwarring rond zijn motieven om in Frankrijk te gaan vechten is ontstaan door de diepgewortelde neiging om de Nederlandse Opstand en de Religieoorlogen in Frankrijk te beschouwen als vergelijkbare, maar op zichzelf staande oorlogen. Echter, Oranje zelf beschouwde ze in essentie als manifestaties van hetzelfde conflict. In dit artikel zal de transnationale kijk van Willem van Oranje ontrafeld worden. Dit perspectief is ook zichtbaar bij veel tijdgenoten en heeft grote invloed gehad op het verloop van de Religieoorlogen in Frankrijk en de Nederlandse Opstand.